Epidemiology of multidrug resistant bacterial organisms and Clostridium difficile in German hospitals in 2014: Results from a nationwide one-day point prevalence of 329 German hospitals. Issue 1 (December 2016) - Huebner, Nils-Olaf; Dittmann, Kathleen; Henck, Vivien; Wegner, Christian; Kramer, Axel
Abstract Background One important aspect in combatting resistance to antibiotics is to increase the awareness and knowledge by epidemiological studies. We therefore conducted a German-wide point-prevalence survey for multidrug resistant bacterial organisms (MDROs) andClostridium difficile (CD) to assess the epidemiology and structure quality of infection control in German hospitals. Method 1550 hospitals were asked to participate and to report surveillance data on the prevalence of Methicillin-resistant and Vancomycin resistantStaphylococcus aureus (MRSA, VRSA/GRSA), Vancomycin resistantEnterococcus faecalis/faecium (VRE), multiresistant strains ofEscherichia coli (EC), Klebsiella spp. (KS), Enterobacter spp . (ES), Acinetobacter spp . (AB) andPseudomonas spp. (PS). as well as CD infections. Results Surveys from 73, 983 patients from 329 hospitals were eligible for analysis. MRSA was the most often reported pathogen (prevalence: 1.64 % [CI95: 1.46-1.82]), followed by 3 multidrug resistant EC (3MRGN-EC) (0.75 % [CI95: 0.60–0.89]), CD (0.74 % [CI95: 0.60–0.88]), VRE (0.25 % [CI95: 0.13–0.37]) und 3MRGN-KS (0.22 % [CI95: [0.15–0.29]). The majority of hospitals met the German recommendations for staffing with infection control personnel. Conclusion The continuing increase in participating hospitals in this third survey in a row indicates a growing awareness to MDROs and our pragmatic approach. Our results confirm that MRSA, 3MRGN-EC, VRE and 3MRGN-KS remain the most prevalent MDROs in German hospitals.